Mycobacterium genavense infection in two species of captive snakes - Ullmann, Leila Sabrina [UNESP]; das Neves Dias-Neto, Ramiro; Cagnini, Didier Quevedo [UNESP]; Yamatogi, Ricardo Seiti; Oliveira-Filho, Jose Paes [UNESP]; Nemer, Viviane; Teixeira, Rodrigo Hidalgo Friciello; Araújo, João Pessoa [UNESP] (Springer Nature, 2016)
Background: Mycobacterium is an important zoonotic agent with companion, livestock and wildlife animals reportedly playing a role as reservoirs. Although its association with reptiles has been described, the disease cycle remains to be fully established, particularly in snakes. Accordingly, this study aimed to report the occurrence of mycobacteriosis with clinical pneumonia in one exotic python snake (Python molurus) and one native green snake (Philodryas olfersii) from the Sorocaba Zoo, São Paulo state, Brazil. Methods: Diagnosis was based on necropsy, histopathological examination, Ziehl-Neelsen stain and immunohistochemistry. Results: Using a nested PCR followed by DNA sequencing and bioinformatics analysis, the causative Mycobacterium species was identified as Mycobacterium genavense. Conclusion:Mycobacterium genavense is an infectious zoonotic agent of animal and public health concerns.
Keywords: Captive snakes; Mycobacterium; Public health